Rhus coriaria induces autophagic and apoptotic cell death in pancreatic cancer cells - Yassine El Mahi; Zohra Nausheen Nizami; Adil Farooq Wali; Aysha Al Neyadi; Mohamed Magramane; Mazoun Al Azzani; Kholoud Arafat; Samir Attoub; Ali H. Eid; Rabah Iratni (Frontiers Media S.A., 2024)
Background:Pancreatic cancer is a leading cause of cancer-related mortality worldwide with increasing global incidence. We previously reported the anticancer effect of Rhus coriaria ethanolic extract (RCE) in triple negative breast and colon cancer cells. Herein, we investigated the anticancer effect of RCE on human pancreatic cancer cells.Methods: Cell viability was measured using Cell Titer-Glo and staining of viable and dead cells based on differential permeability to two DNA binding dyes. Cell cycle distribution and annexin V staining was carried out in Muse cell analyzer. Protein level was determined by Western blot. Tumor growth was assessed by in ovo chick embryo chorioallantoic membrane assay.Results: We found that RCE significantly inhibited the viability and colony growth of pancreatic cancer cells (Panc-1, Mia-PaCa-2, S2-013, AsPC-1). The antiproliferative effects of RCE in pancreatic cancer cells (Panc-1 and Mia-PaCa-2) were mediated through induction of G1 cell cycle arrest, Beclin-1-independent autophagy, and apoptosis. RCE activated both the extrinsic and intrinsic pathways of apoptosis and regulated the Bax/Bcl-2 apoptotic switch. Mechanistically, we found that RCE inhibited the AKT/mTOR pathway, downstream of which, inactivation of the cell cycle regulator p70S6K and downregulation of the antiapoptotic protein survivin was observed. Additionally, we found that RCE-induced autophagy preceded apoptosis. Further, we confirmed the anticancer effect of RCE in a chick embryo xenograft model and found that RCE inhibited the growth of pancreatic cancer xenografts without affecting embryo survival.Conclusion: Collectively, our findings demonstrate that Rhus coriaria exerts potent anti-pancreatic cancer activity though cell cycle impairment, autophagy, and apoptosis, and is hence a promising source of anticancer phytochemicals.